Common good law - Ferguson, Andrew C. (Avizandum Publishing Ltd, 2019)
Common Good Law is the only book to deal with this neglected area of Scots property law. The second edition includes discussion of the important recent case of Portobello Park Action Group Association and of the changes made by the Community Empowerment (Scotland) Act 2015 and the Land Reform (Scotland) Act 2016.